Evolution of a long-duration transpolar arc during very quiet period - He, Fei; Zhang, Xiao-Xin; Li, Jiawei; Yao, Zhonghua; Rong, Zhaojin; Wei, Yong (Frontiers in Astronomy and Space Sciences, 2024)
In this study, we explore the evolution of long-duration transpolar arcs (TPAs) observed during an exceptionally quiet period by the Fengyun-3D and Defense Meteorological Satellite Program satellites on January 17, 2019. Leveraging the extensive field of view of WAI, we captured the complete structure and evolution of the TPA over a very quiet period exceeding 7 hours, with AE<30 nT. The TPA initially manifested at the poleward boundary of the auroral oval in the dawn sector, gradually migrating towards the dusk as the y-component of the interplanetary magnetic field (IMF BY) transitioned from negative to positive. Throughout this phase, the TPA underwent a distortion, transforming from a straight line to an "l-shape". Following a reversal in IMF BY to negative, the TPA retraced its path towards dawn and ultimately dissipated when the IMF turned southward. Of particular interest is the observation that when the TPA approached the noon-midnight line, smallscale spiral structures became apparent within the TPA. This suggests the presence of intricate smallscale magnetic field topologies or plasma instabilities/shears in the source region. These observations highlight the likelihood of complex field and particle dynamics in the high-latitude reconnection region and the twisted tail plasma sheet.